2016
DOI: 10.1080/02646838.2016.1169397
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for tubal sterilisation, regret and depressive symptoms

Abstract: Objective To examine the associations between sterilisation reasons, regret, and depressive symptoms. Study Design Black, Hispanic, and non-Hispanic White US women ages 25–45 who participated in the National Survey of Fertility Barriers (NSFB) and reported a tubal sterilisation surgery were included in the sample for this study (n=837). Logistic regression was used to examine how characteristics of the sterilisation surgery (reasons for sterilisation, time since sterilisation, and new relationship since ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…However, little is known about the topic in Japanese women, and also there are almost no report regarding regret about not receiving permanent contraception. Previous study showed the proportion of women with self‐reported regret about receiving permanent contraception as 1.3%–28% 12–17 . The present study found that 13% of women with permanent contraception expressed self‐reported regret in line with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, little is known about the topic in Japanese women, and also there are almost no report regarding regret about not receiving permanent contraception. Previous study showed the proportion of women with self‐reported regret about receiving permanent contraception as 1.3%–28% 12–17 . The present study found that 13% of women with permanent contraception expressed self‐reported regret in line with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…The psychological consequences of this procedure are not well understood. Some women undergoing this procedure regretted it, which is the cause of distress for them [6,7]. Various studies have shown a high prevalence of anxiety, depression, and sexual dysfunction after TL [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some women undergoing this procedure regretted it, which is the cause of distress for them [ 6 , 7 ]. Various studies have shown a high prevalence of anxiety, depression, and sexual dysfunction after TL [ 7 9 ]. These factors can be effect on women’s QOL.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) women underwent TL at least 1 year ago (2) not being in the postmenopausal period (3) absence of the history of chronic disease includes diabetes, hypertension, thyroid and cardiovascular diseases (4) not using psychiatric medications (5) not having the history of menstrual disorders before sterilization (6) lake of the history of sexual abuse (7) no history of gynecologic surgery except caesarean section and TL (8) not doing breastfeeding.…”
Section: Design and Data Collectionmentioning
confidence: 99%
“…The psychological consequences of this procedure are not well understood. Some women undergoing this procedure are regret, which is the cause of distress for them (6,7). Various studies have shown a high prevalence of anxiety, depression, and sexual dysfunction after TL (6,7).…”
Section: Introductionmentioning
confidence: 99%